AN EVALUATION OF THE CORRELATION BETWEEN ENGLISH LANGUAGE PROFICIENCY AND STUDENTS’ PERFORMANCE IN SCIENCE SUBJECTS AT HIGHER SECONDARY SCHOOL LEVEL IN SINDH - Teevno, Dr. Roshan Ali; Abro, Dr. Allah Dino; Akram, Muhammad (The journal of contemporary issues in business and government, 2021)
The medium of instructions employed for teaching all science subjects up to secondary level is the indigenous language across all public schools of Sindh, but at higher secondary level the medium of instruction is English. Consequently, students face serious problems in learning science subjects. Realizing the gravity of this problem and its adverse effects on other subjects, an empirical study has been conducted which was aimed at measuring correlation between English language proficiency and students’ performance in science subjects. It involves students’ and teachers’ perceptions to find out whether English is truly an obstacle for students especially in science subjects or not, and if so, then to what extent it is so. The population of the study comprised all the teachers and students of Sindh, which was further delimited to Hyderabad, from which a sample of 500 students and 50 teachers was selected through random stratified sampling technique. The data was collected through survey method and questionnaire instruments. The findings showed that there was strong correlation between English language proficiency of students and their performance in science subjects. There was no significant difference between the perceptions of teachers and students regarding the impact of English proficiency on performance of students in science subjects. Even the performance of students in English and science subjects was alike. It also unfolded that the inadequate English language proficiency was such a gigantic stumbling block for students that demoralized a large number of students so much as to drop out prematurely in their studies. They, who managed to overcome this hindrance, get through the exams with merely passing marks or by re-sitting some supplementary exams. Result indicated that this problem was even graver for rural students compared to urban ones. It is suggested that time and energies allocated to improving students’ language proficiency ought to be improved both quantitatively and qualitatively and students should be given leverage to write down their answers partly in English and partly in native language.